24 Hours chronomics of ambulatory blood pressure and its relation with circadian rhythm of 6-sulfatoxy melatonin in night shift health care workers - Anjum, B.; Verma, Narsingh; Tiwari, Sandeep; Mahdi, Abbas A; Singh, Ranjana; Naaz, Qulsoom; Mishra, Saumya; Singh, Prerna; Gautam, Suman; Bhardwaj, Shipra (International Journal of Research in Medical Sciences, 2017)
Background: Night shift workers have altered circadian pattern of blood pressure/heart rate and hormones like melatonin and cortisol. Due to this variation, night shift worker suffers from various cardiovascular disorders and hormonal disturbances. Methods: The Present study was aimed to investigate the effects of rotating night shift on 24 hours chronomics of BP/HR and its relation with 6-sulfatoxy melatonin levels. 62 healthy nursing professionals, aged 20-40 year, performing day and night shift duties were recruited. Each month scheduled to continuous 9 days night shift (12 hours in regular 9 nights, from 20:00 to 08:00); after 9 days night shift they perform remaining duties in day shift and 4 days off in each month. Results: Ambulatory BP and HR were recorded at every 30 min intervals in day time and each hour in night time synchronically with circadian pattern of 6 sulfatoxy melatonin during shift duties. Highly Significant difference was found in double amplitude (2DA) of blood pressure between night and day shift (p<0.001). In night shift, hyperbaric index (HBI) of mean systolic blood pressure was found to be increased at 00-03 am (midnight) while during day shift, peak was found at 06-09 am. Peak melatonin was to be found in early morning as compared to mid night in both the shift. Conclusions: The present study concluded that the desynchronization was appeared during night shift and entrainment of circadian rhythm in the day shift.